Retrospective audit of midazolam dose and intravenous sedation record keeping in a primary care oral surgery service. Issue 1 (March 2022) - Liew, Jonathan; Winston, Michael
Regular and robust audit of conscious sedation practice is key to the delivery of safe and effective patient care in all clinical settings. Analysis of outcomes will help to highlight any necessary modifications to procedures and techniques. The Intercollegiate Advisory Committee for Sedation in Dentistry (IACSD) states that conscious sedation procedures must be the subject of robust and regular audit in which every member within the team takes part. 1 This completed audit cycle highlighted the efficacy of intravenous (IV) midazolam in anxious patients undergoing oral surgical procedures and the suitability for its use in the primary care setting. No patient safety concerns or complications were recorded in this audit and midazolam was administered within the recommended dose range. By the conclusion of two audit cycles, all clinicians providing intravenous sedation within the service were aware of the missing elements in sedation record-keeping and were able to complete accurate contemporaneous records before, during and after conscious sedation, ensuring the continuous delivery of high-quality, safe, and patient-centred care.